DESCRIPCIÓN DE LA HEMBRA Y REDESCRIPCIÓN DEL MACHO DE DICLADOCERA HOPPIENDERLEIN (DIPTERA: TABANIDAE) - González, C. R. (Acta Entomológica Chilena, 2022)
The female and male of Dicladocera hoppi Enderlein is described and illustrated. Comments about relationships of this species are offered.